Penanaman Nilai-Nilai Moral Dalam Cerita Anak Sebagai Upaya Pembentukan Karakter Siswa - Yukhsan Wakhyudi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Abstract: Children’s story is a literary work with readership of children. Through literatur, children get the education that is fun. The story can be an effective means to instill the values of moral education. In addition, the literary work is expected to provide an element of exemplary and moral education for children. Especially in the form of children’s literature fiction featuring models of life by promote the characters as actors life. One of the values presented by the author through the work is the value of moral education. Moral values in literature aimed at educating people to recognize their aesthetic values and character. The purpose of moral education contained in children’s literature in general is to instill character of children to a better direction. Moral values contained in children’s stories include a moral associated with self, others, God, and the natural environment. Those values can be used as the teaching and guidance of man in living his life. Keywords: moral values, children’s story character education.